Literature review of 4Cs skills in engineering education - Amalina Ismail; Nuryazmin Ahmat Zainuri; Noorhelyna Razali; Izamarlina Asshaari (Penerbit Universiti Kebangsaan Malaysia, 2023)
The twenty-first century (21st century) is the era of information fusion where there is dramatic change in the world of knowledge and technology. In this context, engineering education has been based on the knowledge of science, technology, engineering, and mathematics (STEM) to train the future workforce. This paper focuses on understanding the significance of communication, collaboration, creativity, and critical thinking skills (4Cs skills) in engineering education from previous literature. Analysis displays the specific subs-skills within 4Cs skills needed by engineering students and how to inculcate the skills into students. Communication skills are the most demanded skills in industry while creativity skills are the least emphasized skills in engineering education. There are limite studies to compare whether the skills possessed by engineering students meet the industry demand.